Advances in carbohydrate chemistry. - Hudson, C. S. (Claude Silbert), 1881-1952; Cantor, Sidney M.; Peat, Stanley; Stacey, M. (Maurice), 1907-1994 (Advances in carbohydrate chemistry, 1951)
ADVANCES IN CARBOHYDRATE CHEMISTRY VOL 6.